Ability of the Physician Well-Being Index to Identify Residents in Distress - Dyrbye, Liselotte N. (The Accreditation Council for Graduate Medical Education, 2014)
BACKGROUND: Resident well-being impacts competence, professionalism, career satisfaction, and the quality of care delivered to patients. OBJECTIVE: We established normative scores and reported evidence of relationship between the Physician Well-Being Index (PWBI) score to other variables and consequence validity for the PWBI in a national sample of residents, and evaluated the performance of the index after substituting the original fatigue item with an item not associated with driving a car. METHODS: We conducted a cross-sectional survey study of a national sample of 20 475 residents. The survey included the PWBI, instruments assessing mental quality of life (QOL) and fatigue, and items on recent suicidal ideation and medical error. Fisher exact test or Wilcoxon/2-sample t test procedures were used with a 5% type I error rate and a 2-sided alternative. RESULTS: Of 7560 residents who opened the e-mail to participate in the study, 1701 (22.5%) completed the survey. Residents with low mental QOL, high fatigue, or recent suicidal ideation were more likely to endorse each of the PWBI items and a greater number of total items (all P < .001). At a threshold score of ≥ 5, the PWBI's specificity for identifying residents with low mental QOL, high fatigue, or recent suicidal ideation was 83.6%. PWBI score also stratified residents' self-reported medical errors. The PWBI performed similarly using either fatigue item. CONCLUSIONS: The 7-item PWBI appears to be a useful screening index to identify residents whose degree of distress may negatively impact the quality of care they deliver.